Correlation between LncRNA‐LINC00659 and clinical prognosis in gastric cancer and study on its biological mechanism. Issue 24 (3rd November 2020) - Sheng, Yongjia; Han, Chenyang; Yang, Yi; Wang, Jin; Gu, Yanling; Li, Wenyan; Guo, Li
Abstract: Non‐coding RNAs play important roles in tumorigenesis and tumour progression. In previous screening, lncRNA‐LINC00659 (LINC00659) is highly expressed in gastric cancer; however, its role in gastric cancer has not been illustrated yet. In this study, the expression of LINC00659 was detected in cancer tissues and paracancerous tissues of patients with gastric cancer. As a result, LINC00659 expression was increased in gastric cancer tissues, which was closely associated with tumour stage and lymph node metastasis, but was not correlated with age, gender and tissue differentiation. Survival curve analysis showed that patients with low expression of LINC00659 harboured higher overall survival. In vitro, the level of LINC00659 was increased in gastric cancer cells. Afterwards, the expression of LINC00659 was down‐regulated in SGC‐7901 and BGC‐823 cells by plasmid‐mediated si‐LINC00659 transfection. Consequently, the cell invasion ability was weakened, the cell cycle was inhibited, and cell viability was also suppressed. Luciferase reporter gene assay and RNA pull‐down assay showed that LINC00659 could bind to the transcription factor SUZ12, indicating that SUZ12 was a regulatory gene of LINC00659. The overexpression of SUZ12 could resist the roles of si‐LINC00659. In this study, we found that LINC00659 was highly expressed in gastric cancer, which might be related to the regulation of cell proliferation and promotion of cell invasion. Transcription factor, SUZ12, was a regulator of LINC00659. Additionally, LINC00659 could regulate cell cycle and invasion of gastric cancer by promoting the expression of SUZ12.